2011
DOI: 10.1177/1091581811405856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ergothioneine on Clastogenic Potential and Mutagenic Activity

Abstract: L-(+)-ergothioneine has antioxidant and anti-inflammatory properties in vitro and in vivo and has uses as a dietary supplement and as an ingredient in foods, cosmetics, and as a pharmaceutical additive. The clastogenic potential and mutagenic of ergothioneine were assessed in vitro and in vivo. Ergothioneine concentrations up to 5000 μg/mL, with and without metabolic activation, was tested in the chromosome aberration assay with CHL cells and found not to induce structural chromosome aberrations. In the in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Further studies are needed to test the clinical efficacy of ET. However, ET is a safe (to date no studies have demonstrated any evidence of any adverse or mutagenic effects in animals and humans from supplementation , even at extremely high doses ), naturally occurring (present in a wide range of foods), compound that is actively accumulated in the body . Furthermore, the European Food Safety Authority has given approval for ET (Tetrahedron) to be used as a dietary supplement .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to test the clinical efficacy of ET. However, ET is a safe (to date no studies have demonstrated any evidence of any adverse or mutagenic effects in animals and humans from supplementation , even at extremely high doses ), naturally occurring (present in a wide range of foods), compound that is actively accumulated in the body . Furthermore, the European Food Safety Authority has given approval for ET (Tetrahedron) to be used as a dietary supplement .…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the highly variable intake between individuals (358) , however, a number of high-dose studies have indicated that ERG is safe for mammalian consumption at levels far in excess of those likely to be encountered in foodstuffs (125,131,359,360) , and it has been declared safe by relevant committees such as those of the European Food Standards Agency (361,362) . It also lacks any detectable mutagenicity or genotoxicity in such assays, even at very high doses (363,364) .…”
Section: Safetymentioning
confidence: 99%
“…Furthermore, no observable effects were seen on fertility, gestation, and delivery at 725 mg/kg/day, nor were any adverse clinical or physiological indications seen in the litter [ 280 ]. Schauss et al [ 281 , 282 ] also established the absence of any mutagenic and clastogenic effects due to ET administration. US FDA approved the status of “generally recognized as safe” (GRAS), and additionally, the European Food Safety Authority has granted approval for the use of ET as a food supplement even in infants, toddlers, and pregnant and lactating women [ 283 , 284 ].…”
Section: Safety Of Ergothioneinementioning
confidence: 99%